Rapid and accurate dictionary-based T2 mapping from multi-echo turbo spin echo data at 7 Tesla - Emmerich, Julian; Flassbeck, Sebastian; Schmidt, Simon; Bachert, Peter; Ladd, Mark E. (Journal of magnetic resonance imaging, 2019)
Background Using lower refocusing flip angles in multi-echo turbo spin echo (ME-TSE) sequences at ultra-high magnetic field leads to non-monoexponential signal decay and overestimation of T2 values due to stimulated and secondary echoes. Purpose To investigate the feasibility of a fast and accurate reconstruction of quantitative T2 values using an ME-TSE sequence with reduced refocusing flip angles at 7 Tesla, a dictionary-based reconstruction method was developed and is presented in this work. Study Type Prospective. Subjects Phantom measurements with relaxation phantom, four healthy volunteers. Field Strength/Sequence 7 Tesla MRI, multi-echo turbo spin echo (ME-TSE), spin echo (SE), and B1 mapping. Assessment Based on Bloch simulations and the extended phase graph model, signal decay curves were calculated to account for nonrectangular slice profile, B1 inhomogeneity, and reduced refocusing flip angles and stored in a dictionary. Data obtained with an ME-TSE sequence at 7 Tesla were matched to this dictionary to obtain T2 values. To compare the proposed method to reference T2 values, a spin echo sequence with different echo times was used. Statistical Tests Welch's t-test was used to compare T2 values in phantom measurements. Results T2 values obtained with the proposed ME-TSE method coincided with the T2 values from the spin echo experiment in phantom measurements (P = 0.89 for 120° flip angle, P = 0.75 for 180° flip angle). Only for very low B1 transmit fields, a slight overestimation of T2 values was observed. In vivo measurements showed lower T2 values in gray matter (55 ± 2 millisecond) and white matter (39 ± 5 millisecond) compared with literature values of 3 Tesla data. Data Conclusions The proposed dictionary-based ME-TSE approach provided accurate T2 values in short measurement time at 7 Tesla with low specific absorption rate burden due to the reduction of refocusing flip angles. Therefore, it can provide new opportunities in clinical high-field MRI to further improve radiographic diagnosis by using quantitative imaging. Level of Evidence: 1 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2019;49:1253-1262.